1993
DOI: 10.1128/aac.37.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia and prolongation of aminoglycoside-induced postantibiotic effect in Pseudomonas aeruginosa: role of reactive oxygen species

Abstract: Hyperoxia prolongs the postantibiotic effect (PAE) of the aminoglycoside tobramycin in Pseudomonas aeruginosa. We tested the hypothesis that the PAE is prolonged because hyperoxia increases free radical flux while tobramycin inhibits the induction of antioxidant defenses. Exposure ofP. aeruginosa to hyperoxia (100%O 02) for 1 h increased superoxide dismutase, catalase, and glutathione levels. In the presence of tobramycin (1 x the MIC), the induction of antioxidant defenses by hyperoxia was nearly abrogated. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Production of ROS was also recently suggested as the mechanism of antibacterial and antibiofilm activity of other drugs, such as thymoquinone (24), ciprofloxacin, and meropenem (25). Previous studies also related ROS increases with longer PAEs induced by aminoglycosides in Pseudomonas aeruginosa under hyperoxic conditions (26). The photolysis of hydrogen peroxide induced significantly longer PAE in Staphylococcus aureus and Streptococcus salivarius due to the generation of hydroxyl radicals (27).…”
Section: Discussionmentioning
confidence: 95%
“…Production of ROS was also recently suggested as the mechanism of antibacterial and antibiofilm activity of other drugs, such as thymoquinone (24), ciprofloxacin, and meropenem (25). Previous studies also related ROS increases with longer PAEs induced by aminoglycosides in Pseudomonas aeruginosa under hyperoxic conditions (26). The photolysis of hydrogen peroxide induced significantly longer PAE in Staphylococcus aureus and Streptococcus salivarius due to the generation of hydroxyl radicals (27).…”
Section: Discussionmentioning
confidence: 95%
“…6 Hyperoxic states also can potentiate the activity of aminoglycosides, prolong the postantibiotic effect, form free radicals with bactericidal effects and stimulate phagocytosis. 2,7 Amikacin was selected as empirical treatment in this case owing to easier administration and the proportionally high number of cats with nocardiosis displaying susceptibility to amikacin. 1 Thrice-weekly dosing has been reported in treating Mycobacteria spp.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that the duration of PAE was increased for ciprofloxacin against Staphylococcus aureus in media at an acid or alkalic pH compared to broth at pH 7.4, while a reduction in duration of PAE was observed, at an acid pH, for imipenem, ciprofloxacin and aminoglycosides against Echerichia coli and Pseudomonas aeruginosa (Thorburn et al 1996), and no effect of pH was observed for dicloxacillin or gentamicin against Staphylococcus aureus (Gudmundsson et al 1991;. The concentration of Mg2+ has been demonstrated to influence duration of PAE with ofloxacin (Gurdal et al 1990) and hyperbaric oxygen increased PAE twofold when Pseudomonas aeruginosa was treated with tobramycin (Park et al 1991;Park et al 1993). In contrast, a temperature above 37°C had only minimal effects on duration of PAE (Magnusson et al 1995).…”
Section: Test Conditionsmentioning
confidence: 98%